Mangrove Forest Development as Sustainable Vegetation Disaster Mitigation against Coastal Abrasion and Rob Floods in Supporting Regional Resilience in Bekasi Regency - Kurniadi, Anwar; Widana, IDK; Marnani, Christine Sri (Technium Social Sciences Journal, 2023)
The impact of abrasion and tidal flooding will result in public security and human security disturbances. The ultimate impact of a disaster that is not handled properly is that it will disrupt state security. This study uses a qualitative descriptive design method. The purpose of this study was to analyze how far the mitigation of coastal abrasion and tidal flooding using mangrove forest vegetation mitigation and its effect on regional resilience in Muaragembong District, Bekasi Regency. The research was carried out at Mekar Beach, Simple Beach, Bhakti Beach, and Happy Beach, with 16 informants. Research data were analyzed using four steps. The results of the study show that the development of mangrove forests as a mitigation of sustainable vegetation is still being carried out by applying a new method called challenging the ocean currents from behind, and regional resilience is only supported by the existence of good social capital. The conclusion is that even though the development of mangrove forests only strengthens social and community capital, it is able to support the resilience of the Muaragembong region and support ensuring national security.